Primary 3-Month Outcomes of a Double-Blind Randomized Prospective Study - Eidt, John; Petersen, Erika A; Garrett, H. Edward, Jr; Guirguis, Maged; Mekhail, Nagy; Rhee, Peter C; Wu, Jiang; Slavin, Konstantin V; Kapural, Leonardo; Sigdel, Abindra; Kim, Billy; Elshihabi, Said; et al. (Journal of pain research, 2024)
Purpose: This multicenter, randomized, double-blinded, active sham-controlled pivotal study was designed to assess the efficacy and safety of high-frequency nerve block treatment for chronic post-amputation and phantom limb pain. Patients and Methods: QUEST enrolled 180 unilateral lower-limb amputees with severe post-amputation pain, 170 of whom were implanted with the Altius device, were randomized 1:1 to active-sham or treatment groups and reached the primary endpoint. Responders were those subjects who received [greater than or equal to]50% pain relief 30 min after treatment in [greater than or equal to]50% of their self-initiated treatment sessions within the 3-month randomized period. Differences between the active treatment and sham control groups as well as numerous secondary outcomes were determined. Results: At 30-min, (primary outcome), 24.7% of the treatment group were responders compared to 7.1% of the control group (p=0.002). At 120-minutes following treatment, responder rates were 46.8% in the Treatment group and 22.2% in the Control group (p=0.001). Improvement in Brief Pain Inventory interference score of 2.3 [+ or -] 0.29 was significantly greater in treatment group than the 1.3 [+ or -] 0.26-point change in the Control group (p = 0.01). Opioid usage, although not significantly different, trended towards a greater reduction in the treatment group than in the control group. The incidence of adverse events did not differ significantly between the treatment and control groups. Conclusion: The primary outcomes of the study were met, and the majority of Treatment patients experienced a substantial improvement in PAP (regardless of meeting the study definition of a responder). The significant in PAP was associated with significantly improved QOL metrics, and a trend towards reduced opioid utilization compared to Control. These data indicate that Altius treatment represents a significant therapeutic advancement for lower-limb amputees suffering from chronic PAP. Keywords: post-amputation pain, phantom limb pain, neuromodulation, peripheral nerve stimulation, high-frequency nerve block